ABIOGENIC ORIGIN OF HYDROCARBONS: AN HISTORICAL OVERVIEW - Glasby G.P. (My University, 2006)
The two theories of abiogenic formation of hydrocarbons, the Russian-Ukrainian theory of deep, abiotic petroleum origins and Thomas Gold's deep gas theory, have been considered in some detail. Whilst the Russian-Ukrainian theory was portrayed as being scientifically rigorous in contrast to the biogenic theory which was thought to be littered with invalid assumptions, this applies only to the formation of the higher hydrocarbons from methane in the upper mantle. In most other aspects, in particular the influence of the oxidation state of the mantle on the abundance of methane, this rigour is lacking especially when judged against modern criteria as opposed to the level of understanding in the 1950s to 1980s when this theory was at its peak. Thomas Gold's theory involves degassing of methane from the mantle and the formation of higher hydrocarbons from methane in the upper layers of the Earth's crust. However, formation of higher hydrocarbons in the upper layers of the Earth's crust occurs only as a result of Fischer-Tropsch-type reactions in the presence of hydrogen gas but is otherwise not possible on thermodynamic grounds. This theory is therefore invalid. Both theories have been overtaken by the increasingly sophisticated understanding of the modes of formation of hydrocarbon deposits in nature.
Keywords: ABIOGENIC HYDROCARBONS; RUSSIAN-UKRAINIAN THEORY; THOMAS GOLD